Integrating Experiential Marketing Concepts into Business Education: A Case Study in the Jewelry Industry - Xu, Yuanchun; Wang, Shaowen (Journal of Buddhist Education and Research (JBER), 2025)
With the acceleration of global economic integration, the jewelry industry, as an important component of the high-end consumer goods market, is facing increasingly fierce market competition. Traditional marketing methods are no longer able to meet the increasingly diverse needs of consumers, and experiential marketing, as an emerging marketing concept, is gradually receiving widespread attention from jewelry companies. This article is based on the stimulus response model and empirically tests the impact path and mechanism of sensory experience and emotional experience on consumer purchasing behavior through regression analysis, and verifies the mediating role of consumption ability. The study used quantitative methods and collected 272 valid sample data. The results indicate that both sensory and emotional experiences have a significant positive impact on purchasing behavior, with emotional experience having a more prominent influence (β=0.482, p<0.001). In addition, consumer power plays an important mediating role in the impact of both factors on purchasing behavior. The study provides strategic recommendations for jewelry brands to strengthen sensory design and deepen emotional marketing, in order to enhance brand influence and consumer purchase intention.